Wpływ czynników pozaprzyrodniczych na zmiany struktury krajobrazu rolniczego Regionu Północno-Zachodniego w ostatnim dwudziestoleciu - Markuszewska, Iwona (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
This paper presents preliminary results of the study on agricultural landscape structure changes as a consequence of the influence of non-natural factors. The study region includes provinces of the North-Western Region while the time span covers the years 1990–2010. Quantitative analysis of farmland use changes, which were based on Central Statistical Office data, were made. Moreover, selected indicators of agriculture characteristic as well as Driving Force – Pressure – State – Impact – Response approach were used. The study showed that due to increasing pressure of the intensive manner of arable land management, the durability and stability of landscape structure are under potential threat. This is because the economic benefits associated with increasing productivity are not always favourable from the point of view.
Keywords: agricultural landscape structure; non-natural factors; North-Western Region